Island Fantasia Imagining Subjects on the Military Frontline between China and Taiwan - Lin, Wei-Ping (Social Sciences, 2021)
This in-depth study of the Matsu islands between China and Taiwan charts their sudden transition from a forbidden outpost in the Qing period to a military frontline during the Cold War and the Communist-Nationalist conflict, and showcases the cultural vibrancy of the people as they imagine their future. ?